ANALYSIS OF ELECTROMAGNETIC RADIATION FOR FOUR DIFFERENT TRANSMISSION POWER STATIONS AREAS OF NIGERIA - Haruna, Ali; Olatunbosun, R. O.; Ibiyemi, A. A.; Awodugba, A. O. (FUDMA Journal of Sciences, 2023)
Exposure to electric field and magnetic field can result in serious health effect which is our major concern in this research work. The measurement of electromagnetic field strength required for the evaluation of electromagnetic pollution from power lines has been recommended by International Radiation Protection Association (IRPA). In this research work, the study of electromagnetic radiation emanated from high tension transmission lines and 330 KV from Osogbo power transmission station, Egbin power station, Jebba power station and Kaduna power transmission stations were considered as case study. This research work was evaluated on the platform of the safety limits recommended by International Committee on Non-ionizing Radiation Protection. The electric field and the magnetic field within the power transmission stations with distance varying between 10m and 100m were measured using electro smog meter. It was observe that the electric field and the magnetic field are higher within 10m to 70m but become greatly attenuated beyond the 80m.The lowest electric field strength measured for power stations are 6.178 V/m, 8.212 V/m, 5.11 V/m and 4.000 V/m from Jebba high tension line, Egbin power stations, Osogbo and Kaduna power lines. The highest electric field strength measured for each power stations are 12.001 V/m, 11.041V/m, 10.941 V/m and 11.00 V/m for Egbin power station, Jebba power station, Osogbo power station and Kaduna power station respectively. The highest magnetic field strength, the measured from each stations are 9.146 A/m, 9.000 A/m, 8.912 A/m and 8.003 A/m respectively while the lowest measurements are 6.112 A/m, 4.341 A/m,